Pengembangan Media Video Bimbingan Konseling untuk Mengurangi Perilaku Bullying - Agrianur Rahman; Farida Aryani; Abdullah Sinring (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
The research aims to (1) the description of development needs of Guidance and Counseling Video Media to Reduce Bullying Behavior, (2) the prototype of Guidance and Counseling Video Media to Reduce Bullying Behavior which is valid and acceptable, (3) the acceptance of Guidance and Counseling Video Media to Reduce Bullying Behavior in SMAN 5 Makassar. The research was development research or research and development which was based on research stages by Borg and Gall. The research employed collecting data technique through interview and scale. The results of research revealed that (1) the description of needs level of Guidance and Counseling Video Media to Reduce Bullying Behavior showed that the video media very important and needed, (2) the prototype of Guidance and Counseling Video Media developed was already valid and acceptable to Reduce Bullying Behavior, (3) the acceptance of Guidance and Counseling Media Video which was given to 10 students in small group test showed that there was change of bullying behavior level before and after viewing Guidance and Counseling Video Media. This meant that guidance and counseling media video could reduce bullying behavior.